Mechanisms and Functions of Mitophagy and Potential Roles in Renal Disease - Zuo, Zhenying; Jing, Kaipeng; Wu, Hongluan; Wang, Shujun; Ye, Lin; Li, Zhihang; Yang, Chen; Pan, Qingjun; Liu, Wei Jing; Liu, Hua-feng (Frontiers in Physiology, 2020)
Mitophagy is an evolutionarily conserved process to selectively remove damaged or unnecessary mitochondria via the autophagic machinery. In this review, we focus on recent advances in the molecular mechanisms of mitophagy and how mitophagy contributes to cellular homeostasis in physiological and pathological contexts. We also briefly review and discuss the crosstalk between mitophagy and renal disease, highlighting its modulation as a potentially effective therapeutic strategy to treat kidney diseases such as acute kidney injury (AKI), diabetic kidney disease (DKD), and lupus nephritis (LN).